An Unusual Adenomatoid Tumor of Fimbria with Pronounced Psammoma Bodies in a BRCA Positive Patient as a Pitfall for Carcinoma on Frozen Section. (21st November 2018) - Lee, Christine M.; Moh, Michelle; Sullivan, Peggy S.; Moatamed, Neda A.
Abstract : Background . BRCA gene mutations significantly increase the risk of breast and ovarian cancers where the lifetime risk of the ovarian cancer is about 40%. Therefore, many women with such mutations undergo prophylactic bilateral mastectomy and salpingo-oophorectomy. About 5-6% of these individuals display occult carcinomas in tubo-ovarian locations of which over 85% are tubal in origin. The objective of this case study was to emphasize emergence of benign lesions mimicking cancer under these circumstances. Case Report . We present a case with positive BRCA1 mutation who underwent the prophylactic procedure where a small mass was identified in her fallopian tube. Our initial encounter with this tumor was during intraoperative consultation. The tumor was associated with extensive psammoma bodies arranged in closely packed small tubules, mimicking serous carcinoma. Frozen section limitations including artifact, time constraint, and lack of ancillary studies as well as the clinical history further complicated our diagnostic assessment, which was deferred. A diagnosis of adenomatoid tumor was rendered on permanent sections. Conclusion . It is important to be familiar with this morphologic presentation of adenomatoid tumor as it is a pitfall for carcinoma, particularly on frozen section, and inaccurate diagnosis could lead to further unnecessary extensive procedures.